The Decision Relevance of Loan Fair Values for Depositors - CHEN, QI; VASHISHTHA, RAHUL; WANG, SHUYAN (Journal of Accounting Research, 2025)
ABSTRACT Using a large sample of U.S. commercial banks from 1994 to 2019, we find that loan fair values are highly relevant for depositor decision making. A one‐standard‐deviation decrease in loan fair value performance is associated with more than 10% lower uninsured deposit flows than the sample average. Information in fair values about loan credit quality is quite limited and cannot account for the bulk of the relevance. Instead, consistent with models of bank fragility, the relevance seems to stem more from information on the decline in loan liquidation values, triggering panic‐based withdrawals motivated by (self‐fulfilling) expectations of withdrawals by other depositors. The findings inform the cost‐benefit tradeoff of reporting loan fair values.